Development of E-Book Multimedia Model to Increase Critical Thinking of Senior High School Students - Suparno, Suparno (Dinamika Pendidikan, 2017)
This study aims to develop the interactive e-book multimedia model to improve the students' critical thinking ability (KBK). Critical thinking is very important to develop because it provides a high level of reasoning thinking that provides permanent experience to students through conscious and controlled decision making in a rational, reflective, responsible manner with the optimization of potential. Flash-based e-book media is capable of interactively loading videos, pictures, practice questions and learning with directed directions from the teacher. The research method developed is research and development. The output products are learning plan, KBK evaluation question, flash-based interactive e-book multimedia, and quasi experiment to see media effectiveness to KBK. The results showed that e-book multimedia is able to significantly increase the KBK of high school students in economic learning.